Alternate and Incidental Diagnoses on Noncontrast-Enhanced Spiral Computed Tomography for Acute Flank Pain - Ather, M Hammad; Faizullah, Kulsoom Faizullah; Achakzai, Ilyas Achakzai; Siwani, Rizwan; Irani, Fariah (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:ArialUnicodeMS; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"Arial Unicode MS"; mso-font-charset:129; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:1 151388160 16 0 524288 0; @font-face font-family:"\@ArialUnicodeMS"; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:129; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:1 151388160 16 0 524288 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: Our aim was to determine the incidence and spectrum of significant alternate or incidental diagnoses established or suggested on spiral computed tomography (CT) in a large series of patients with suspected renal colic. Materials and Methods: Records of all patients that had undergone spiral CT (5-mm to 7-mm slice thickness) for acute flank pain during a 5-year period were reviewed. The radiological diagnoses of urinary calculi and obstruction as well as clinical entities not suspected otherwise were analyzed. Results: A total of 4000 CTs had been performed in the evaluation of acute flank pain. Urinary calculi had been identified in 3120 patients (78.0%). There were 398 patients (9.9%) who had an alternate cause of flank pain or an incidentally detected condition on CT. Of these patients, 102 (25.6%) had more than one additional finding. A total of 153 clinical conditions had been identified mimicking flank pain secondary to calculus and obstruction. In 47 patients (1.2%), incidental solid masses had been detected. Conclusion: Spiral CT is a valuable technique in the evaluation of acute flank pain with uncertain clinical diagnosis. A wide spectrum of alternate and additional diagnoses including abdominal solid organ tumors and other significant abdominal conditions such as pancreatitis can be established or suggested on spiral CT performed for suspected acute urinary colic.